Perception on E-CRM features for airline websites in Malaysia: some empirical evidence - Ismail, Nor Alina; Hussin, Husnayati (Institute for Strategic and Sustainable Accounting Development (ISSAD), School of Accountancy, Universiti Utara Malaysia, UUM Sintok, Kedah, Malaysia, 2015)
Currently, customers increasingly choose the websites to search and purchase flight tickets. This paper attempts to investigate the website quality in terms of e-CRM features that support online transactions for the purchase of flight tickets in Malaysia. The focus is on the features that support pre-purchase, purchase and post-purchase activities of online transaction. Using a survey questionnaire method, a total of 508 responses were collected among those who have experience using Malaysia airlines websites to purchase e-flight tickets. Based on descriptive analysis, the findings revealed that the respondents were generally satisfied with the airline e-ticketing services offered by the top five Malaysia airlines. Related to e-CRM features, it was found that most online buyers generally found the e-CRM features supporting the pre-purchase, purchase and post-purchase as useful. Specifically, they perceived the websites features supporting their purchase activity are most satisfactory, compared to those supporting pre-purchase and post-purchase. This study is among a few that provides empirical evidence on this issue which Malaysia-based airline companies may use to provide better online customer services in the future.